RECIPROCAL TEACHING: ONE OF THE METHODS FOR POOR COMPREHENDERS - Yawisah, Umi (JURNAL PEDAGOGY, 2013)
Abstract : Reciprocal teaching is aÂ  methodÂ  which emphasizesÂ  the studentsâ cognitive and meta cognitiveÂ  domains for it covers the structural process of the instruction. TheÂ  whole elements within the procedure enable the students toÂ  choose the strategy, plan, monitor, and evaluate their ownÂ  activities. Furthermore, the procedures integrated in this method Â are believed toÂ  enhance the studentsâ thinking process. The method, introduced byÂ  Palinscar and Brown, belongs to cooperative learning in that the studentsâ thinking process in learning is expressed through a natural dialogue. This method is designed to improve the studentsâ competency in text reading while those students find it difficult to comprehend the content of the text. The method also encourages the students to apply such four strategies as predicting, summarizing, questioning, and clarifying.Â Key words: reciprocal teaching, method, reading, thinking process